Unravelling Cooperative Learning in Higher Education - Raymond Chee-Yen Loh; Chin-Siang Ang (Research in Social Sciences and Technology- OpenED Network, 2020)
Teaching and learning have evolved over the years. While the use of lecture is still the dominant mode of teaching in educational institutions, there has been consensus that students need to be active in learning, for which traditional styles of teaching may not be well suited. This calls for an alternative instructional mode: cooperative learning to promote active learning among students. In higher education, interest in cooperative learning has gained momentum since the early 1980s, and this kind of teaching and learning can be conducted in many ways. The purpose of this study is to provide an overview of existing evidence pertinent to cooperative learning. In this review, cooperative learning is defined and elements inherent in this pedagogy are discussed. Theoretical perspectives relating to cooperative learning are also outlined. The outcomes pertaining to cooperative learning are then presented, followed by the influence of context on cooperative learning. This review is organized and structured as such to serve as a basis of reference for further research in the field.